2014
DOI: 10.4048/jbc.2014.17.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Subtype Is a Predictive Factor of Nonsentinel Lymph Node Involvement in Sentinel Node-Positive Breast Cancer Patients

Abstract: PurposeThis study aimed to identify the effect of breast cancer subtype on nonsentinel lymph node (NSLN) metastasis in patients with a positive sentinel lymph node (SLN).MethodsThe records of 104 early breast cancer patients with a positive SLN between April 2009 and September 2013 were retrospectively evaluated. All patients underwent axillary lymph node dissection. The effects of the tumor subtype (luminal A, luminal/HER2+, human epidermal growth factor receptor 2 [HER2] overexpression, and triple-negative) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Furthermore, tumor size was found to be a major determinant of axillary metastasis development in HER2 positive and ER positive (either HER2 negative or positive) subgroups. Other authors have also demonstrated a higher risk of lymph node metastasis in patients with HER2 overexpression 31,32 . The present study did not find this correlation, which can be explained by the small number of patients with HER2+.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, tumor size was found to be a major determinant of axillary metastasis development in HER2 positive and ER positive (either HER2 negative or positive) subgroups. Other authors have also demonstrated a higher risk of lymph node metastasis in patients with HER2 overexpression 31,32 . The present study did not find this correlation, which can be explained by the small number of patients with HER2+.…”
Section: Discussionmentioning
confidence: 85%
“…Some of the aforementioned factors were used in combination to constitute nomograms like MD Anderson, MSKCC, and Helsinki (21,28,29). These three nomograms are widely used in research studies and readily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 104 cases of SLN biopsy, of which 48% had metastases in NSLNs, concluded that the primary tumor diameter and the rate of positive lymph nodes were prognostic factors for the positivity of the NSLNs. At the same time, positive NSLNs are associated with HER2 + and HER2 overexpression luminal molecular profile of the primary tumor (20).…”
Section: Discussionmentioning
confidence: 94%
“…These parameters are similar to those studied in the literature before and after applying the Z0011 criteria (Table 2). Apart Barranger E [15] 337 SLNB/71 ALND Tumor histological type, tumor diameter, number of +SLN, LNR Van la Parra RF [16] 56 studies ECE, >1+SLN, LNR>0.5 Studies published after the Z0011 trial Boler DE [17] 332 SLNB/116 ALND Tumor histological type, presence of LVI, tumor diameter Mittendorf EA [18] 509 ALND after SLNB Number of excised SLN, Number of +SLN, ECE, tumor histological type and tumor diameter Kuo YL [19] 324 ALND after SLNB Tumor histological type, tumor diameter, number of +SLN Gülben K [20] 104 SLNB/50 ALND Tumor diameter, LNR, Tumor molecular profile Toshikawa C [21] 358 SLNB/ 54 ALND Tumor diameter Padmanabhan N [22] 334 SLNB/ 64 ALND ECE, number of +SLN Van den Hoven I [23] 513 Diameter of the sentinel SLN metastasis Schwentner L [24] 324 ECE Table 2. Similar studies in the literature highlighting prediction factors for the positivity of nonsentinel lymph nodes (SLNB-Sentinel lymph node biopsy, SLN-Sentinel lymph node, ALND-axillary lymph node dissection, LNR-lymph hode ratio, ECE extracapsular extension, LVI-lymphovascular invasion)…”
Section: Discussionmentioning
confidence: 99%